Recommendations to counselors in dealing with clients suffering from depressive mental health issues - Kamaruddin, Mohd. Shahrul; Ma’rof, Aini Azeqa (State University of Medan, 2022)
Depression is a common mental health disorder. According to a survey by the Ministry of Health Malaysia (MOH), 1 in 5 adolescents tend to suffer from depression. Depression is characterized by persistent sadness and a lack of interest or enjoyment in their previously beneficial or enjoyable activities. Thus, as a counselor or therapist, self -preparation such as preparation in terms of skills, knowledge of depression issues and preparation in dealing with individuals with depressive illness is very important to help them rise again. The main concept of this paper discusses recommendations that can be referred to by counselors or therapists in dealing with clients who have mental health issues especially depression issues. Efforts in screening for depression issues and identifying the level of depression are also discussed in this paper. The researcher also used the method by making self -reflection based on observations, as well as reading the literature for this study. Thus, the implications of the discussion are also stated in this paper